Pengaruh Carbon Emission Disclosure dan Good Corporate Governance Terhadap Nilai Perusahaan - Sufiati, Zalikha; Taqwa, Salma (Universitas Negeri Padang, 2025)
This study aims to analyze the effect of carbon emission disclosure and good corporate governance on firm value in the manufacturing sector in Indonesia. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the period 2021-2023. The sampling technique used purposive sampling method, so that 42 companies were obtained as samples with a total of 126 observations. The data used is secondary data derived from annual reports and company sustainability reports. Firm value is measured using Tobin's Q ratio. Good Corporate Governance variables are proxied through the proportion of independent commissioners, the number of audit committees, and the level of institutional ownership. The results of panel data regression analysis show that disclosure of carbon emissions, independent board of commissioners, and audit committee have no significant effect on firm value. In contrast, institutional ownership has a positive influence on firm value. These findings contribute to understanding the role of sustainability and governance factors in enhancing firm value, particularly in the context of the manufacturing industry in the Indonesian capital market.